Pengaruh Teknik Relaksasi Otot Progresif Terhadap Tingkat Stres Kerja Pada Perawat di Instalasi Gawat Darurat - Yunita Gabriela Madu; Mery Solon; Jenita Laurensia Saranga'; Firmawati Naim; Fransiska Imelda Poa (Jurnal Keperawatan Florence Nightingale, 2024)
Stress is a physical and emotional disturbance resulting from a mismatch between the capacity, resources and needs of employees originating from the work environment. This will trigger stress due to workload which is sometimes considered inappropriate for physical, psychological and emotional conditions. The aim of this research is to determine the effect of progressive muscle relaxation techniques on work stress in emergency room nurses at Stella Maris Hospital Makassar. This research was carried out at Stella Maris Hospital Makassar since September 2022 using a pre-experimental research type and One Group Pretest Posttest Design. The population in this study were all 19 emergency room nurses at Stella Maris Hospital in Makassar using a non-probability technique, namely Total Sampling. The measuring tools used were the DASS 42 questionnaire to measure nurses' stress levels and observation sheets to assess the implementation of progressive muscle relaxation techniques. The data was tested using the alternative Wilcoxon test because the data scale used was numerical data so that the research results showed that 19 respondents had decreased stress scores or levels after the progressive muscle relaxation technique intervention. Based on the results of the Wilcoxon test, the value of p = 0.000 < a 0.005 was obtained, so it can be concluded that there is an influence of progressive muscle relaxation techniques on the level of work stress in nurses in the Emergency Room at Stella Maris Hospital, Makassar.